2016
DOI: 10.1016/j.scitotenv.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Sewage sludge stabilisation and fertiliser value in a silvopastoral system developed with Eucalyptus nitens Maiden in Lugo (Spain)

Abstract: Copper (Cu) is one of the heavy metals with highest proportion in sewage sludge. In Europe, sewage sludge should be stabilised before using it as a fertiliser in agriculture. Depending on the stabilisation process, sewage sludge has different Cu contents, and soil Cu incorporation rates. This study was undertaken to examine the effect of fertilisation with different types of sewage sludge (anaerobic, composted, and pelletised) on the concentration of total and available Cu in the soil, the tree growth, the pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
(24 reference statements)
1
5
0
Order By: Relevance
“…Soil analysis results revealed a change in soil pH after the treatments application. Many works reported an increase (Bayoumi Hamuda et al, 2009;Ferreiro-Domínguez et al, 2011) or a decrease (Mosquera-Losada et al, 2016;Singh and Agrawal, 2007) in soil pH. In the present work, acidification occurred in treated sandy soil samples, probably due to both the lower pH of SSADs and the nitrogen mineralization (Rasouli-Sadaghiani and Moradi, 2014).…”
Section: Substrates Analysessupporting
confidence: 53%
“…Soil analysis results revealed a change in soil pH after the treatments application. Many works reported an increase (Bayoumi Hamuda et al, 2009;Ferreiro-Domínguez et al, 2011) or a decrease (Mosquera-Losada et al, 2016;Singh and Agrawal, 2007) in soil pH. In the present work, acidification occurred in treated sandy soil samples, probably due to both the lower pH of SSADs and the nitrogen mineralization (Rasouli-Sadaghiani and Moradi, 2014).…”
Section: Substrates Analysessupporting
confidence: 53%
“…Several soil properties, such as bulk density, porosity, and water-holding capacity showed improvement because of the addition of SSC 38 40 . SSC can also play an important role in regulating soil pH 22 , 41 . In general, the changes in the physicochemical parameters of soil became more pronounced with increasing rates of SSC application 40 .…”
Section: Discussionmentioning
confidence: 99%
“…The positive influence of the application of SSC on soil properties generally resulted in a positive effect on the growth and nutrient uptake of a wide variety of plants 4 , 40 , 41 . Several studies have reported better growth for different woody plants following the application of SSC, including Larix decidua 43 , Paeonia suffruticosa 9 , and Pinus radiata 44 .…”
Section: Discussionmentioning
confidence: 99%
“…In relation to economics, we observed a study focused on analyzing the environmental and economic profitability of livestock grazing on farms under a silvopastoral system [79]. Finally, the most relevant species were Quercus ilex, Quercus rubra, Pinus radiata, Fraxinus excelsior, Prunus avium, Pinus pinea, Eucalyptus nitens, and Betula pubescens [79][80][81][82][83][84][85].…”
Section: Country Classification By Publicationsmentioning
confidence: 99%